Open- vs. closed-chest pig models of donation after circulatory death - Hubacher, Valentin; Egle, Manuel; Graf, Selianne; Arnold, Maria; Segiser, Adrian; Sanz, Maria Nieves; Casoni, Daniela; Garcia Casalta, Luisana; Nettelbeck, Kay; Mihalj, Maks; Siepe, Matthias; Kadner, Alexander; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: During DCD, cardiac grafts are exposed to potentially damaging conditions that can impact their quality and post-transplant outcomes. In a clinical DCD setting, patients will have closed chests in most cases, while many experimental models used open-chest conditions. We therefore aimed to investigate and characterize differences in open-versus closed-chest porcine models.Methods: Withdrawal of life-sustaining therapy (WLST) was simulated in anesthetized, juvenile, male pigs by stopping mechanical ventilation following administration of neuromuscular block. Functional warm ischemic time (fWIT) was defined to start when systolic arterial pressure was <50 mmHg. Hemodynamic changes and blood chemistry were analysed. Two experimental groups were compared: i) an open-chest group with sternotomy prior to WLST, and ii) a closed-chest group with sternotomy after fWIT.Results: Hemodynamic changes during the progression from WLST to fWIT were initiated by rapid decline in blood oxygen saturation and a subsequent cardiovascular hyperdynamic period with temporary elevations in heart rates and arterial pressures in both groups. Subsequently, heart rate decreased, as did systolic arterial pressure until fWIT was reached. Pigs in the open-chest group displayed a more rapid transition to the hyperdynamic phase (HD) after WLST with peak heart rate and peak rate-pressure product occurring significantly earlier. Furthermore, the HD phase duration tended to be shorter and less intense (lower peak rate-pressure product) in open-versus closed-chest groups.Discussion: Progression from WLST to fWIT was more rapid, and the hemodynamic changes tended to be less pronounced, in the open-chest open-vs. closed-chest group. Our findings support clear differences between open-and closed-chest models of DCD. Therefore, recommendations for clinical DCD protocols based on findings in open chest models must be interpreted with care.